Interactive Media with A Generative Learning Model based on SETS to Improve Students' Critical Thinking Skills - Michelly Fathimatuzzahra Suhengki; Akmam Akmam; Suhengki; Desnita; Fatni Mufit (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Quality education is a key factor in producing competent human resources capable of addressing the challenges posed by the rapid advancement of science and technology in the era of globalization. In the context of 21st-century learning, students are not only required to master conceptual knowledge but also to develop various higher-order thinking skills, one of which is critical thinking. Based on this premise, this study aims to develop an interactive learning media using the Generative Learning Model with a Science, Environment, Technology, and Society (SETS) approach to enhance students’ critical thinking skills. This study employed a Research and Development (R&D) design using the ADDIE Model. The research sample consisted of 49 senior high school students. The research subjects included five learning media experts, while the trial participants consisted of three physics teachers and 52 tenth-grade students. Data were collected using questionnaires and tests, with instruments consisting of questionnaire sheets and test items. Data analysis techniques included qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis. The results indicate that the developed interactive learning media based on the Generative Learning Model with the Science, Environment, Technology, and Society (SETS) approach demonstrates a very high level of feasibility in terms of validity, practicality, and effectiveness. Based on these findings, it can be concluded that the interactive renewable energy learning media developed through the Generative Learning Model and Science, Environment, Technology, and Society (SETS) approach is effective in improving students’ critical thinking skills.